MODEL OF DEVELOPMENT OF PEDAGOGICAL COMMUNICATION IN POSTGRADUATE EDUCATION - Сафарян, Світлана; Кузьменчук, Ірина (SWorldJournal, 2024)
one of the main tasks of modern postgraduate education is the development of the professional competence of teachers, which is impossible without the developed abilities and skills of pedagogical communication. The article is devoted to the consideration